POLITIK WACANA DI MEDIA SOSIAL TWITTER MENJELANG PEMILIHAN PRESIDEN INDONESIA 2014 - Tian Belawati (Lakon : Jurnal Kajian Sastra dan Budaya, 2015)
Most of Indonesian politicians used internet and social media for campaign. The phenomena of twitwar, counter attack tweet, and black campaign using ironical and sarcasm words were massively appearing during presidential election which has been held in July 2014. The black campaign which was appearing pointed to represent characters of an actor or a candidate of president. This study is aimed to answer what topics written by cyber activists and politicians during January to April 2014, to find the discourse politics in representing the actors, and also to map the democratic action during campaign period in the twitter. The subjects of this study were twitter accounts of @Fadjroel, @PartaiSocMed, and @TrioMacan2000. The critical discourse analysis within critical linguistics approach by Theu Van Leeuwen was used to analyze the marginalization and the discourse politics. Theory of cyber culture, cyber sphere, and democratic in cyber space were used to be frameworks. The result tells that the sarcasm and ironical words were used to be discourse poltics in representing the actors. The ironical and sarcasm words were used as democratic form in social media which made youth as target readers considering youth were the most active users.